[OP.7C.06] VASCULAR TRANSCRIPTOME PROFILING IDENTIFIES SPHINGOSINE KINASE 1 AS A KEY MODULATOR OF ANGIOTENSIN II-INDUCED HYPERTENSION. (September 2016) - Siedlinski, M.; Szczepaniak, P.; Nosalski, R.; Ludwig-Galezowska, A.; Mikolajczyk, T.; Filip, M.; Wolkow, P.; Guzik, T.
Abstract : Objective: Vascular dysfunction is an important element of hypertension pathogenesis and involves changes in numerous pathways important for disease development and target organ damage. We hypothesized that angiotensin II (AngII) affects transcriptome in the vasculature in a region-specific manner, which may help to identify genes causally related to the development of AngII-induced hypertension. Design and method: Transcriptome of thoracic aorta, abdominal aorta and mesenteric arteries was profiled in 12 C57BL/6J wild-type (WT) hypertensive mice infused with AngII at a 490 ng/kg/min. dose for 2 weeks and 12 control, buffer infused mice using Illumina WG-6 v2.0 chip. Tissue organ bath experiments were performed using 750TOBS instrument. Sphingosine kinase 1 (Sphk1)−/− and appropriate WT mice were studied. Results: Among over 16, 000 RNA transcripts detected 21.5% were significantly (FDR corrected p < 0.05) differentially expressed in thoracic aorta between hypertensive and control mice, while such proportion was lower for abdominal aorta (0.3%) or mesenteric arteries (1.4%). Gene set enrichment and subsequent leading edge analyses performed on thoracic aorta transcriptome identified 4 genes present in the highest number of significantly AngII-affected biological pathways. Among them Sphk1 showed the highest significant expression fold change and independent quantitative PCR confirmed induction of Sphk1 (Induction Fold (IF) = 3.8, p < 0.001) and showed no change in expression of its isoenzyme Sphk2 (IF = 1.1, p = 0.42) in hypertensive as compared to control mice. Ex vivo inhibition of sphingosine-1-phosphate (S1P) synthesis significantly reduced vasoconstriction in response to KCl, phenylephrine or prostaglandin F2α (PGF2α) in intact and endothelium-denuded aortic rings. Sphk1−/− mice developed less severe AngII-induced hypertension (systolic BP 168 ± 3 vs. 180 ± 3 mmHg, p < 0.05) and lower heart hypertrophy as compared to WT hypertensive mice. Normotensive and hypertensive Sphk1−/−mice had significantly lower aortic contraction in response to PGF2α and KCl respectively as compared to appropriate WT animals. Significantly lower amounts of CD25+ and CD69+ T lymphocytes in the spleen and periaortic adipose tissue of hypertensive Sphk1−/− mice as compared to hypertensive WT mice were observed. Conclusions: This study shows that S1P is one of the key mediators of AngII-induced hypertension in vivo.